The Abuse of Men by Women - Đurđević, Sanja K.; Đurđević, Ana S.; Lukić, Aleksandar R. (Collection of Papers of the Faculty of Philosophy in Priština, 2022)
Although numerous studies in the past have shown that men are more often seen as perpetrators of domestic and sexual abuse, clinicians and researchers have recently begun to critically consider the problem of intimate and sexual violence committed by women towards men. Despite the controversial debate over whether women are violent towards their husbands and partners, many research papers have shown that there is a prevalence of such violence. In addition, many studies have highlighted gender differences in the commission of domestic violence in terms of the different reasons and contexts in which violence occurs. This paper aims to present the latest results of research on risk factors, typologies, and motives of women perpetrators of violence in relationships, as well as to improve our understanding of the etiology and complexity of such violence. The first part of the paper explains in detail the typology and prevalence of violence against men, as well as the psychological and other characteristics of women perpetrators. The second part deals mainly with the causes and motives of women‘s violent behaviour towards men. The last section is dedicated to the effects of treatment and possible improvements. The conclusion emphasizes the importance of this topic and gives some recommendations for resolving the above issues.
Keywords: partner violence; sexual violence; female perpetrators